The African Association for Lexicography: After Ten Years - Alberts, Mariëtta (Lexikos, 2005)
ABSTRACT: This year it has been ten years since the establishment of AFRILEX. After an expla-nation of what led to its forming, this article gives a short overview of its composition and activi-ties.Keywords: AFRICAN ASSOCIATION FOR LEXICOGRAPHY (AFRILEX), AFRICAN LAN-GUAGES ASSOCIATION OF SOUTH AFRICA (ALASA), BUREAU OF THE WOORDEBOEK VAN DIE AFRIKAANSE TAAL (WAT), DICTIONARY OF SOUTH AFRICAN ENGLISH (DSAE), LINGUISTIC ASSOCIATION OF SOUTHERN AFRICA (LSSA), NATIONAL LEXICOGRAPHY UNITS (NLUs), PAN SOUTH AFRICAN LANGUAGE BOARD (PanSALB)*****OPSOMMING: Die African Association for Lexicography: Ná tien jaar. Vanjaar is dit tien jaar sedert die totstandkoming van AFRILEX. Na 'n verduideliking wat tot sy stigting gelei het, gee die artikel 'n kort oorsig van sy samestelling en werksaamhede.Sleutelwoorde: AFRICAN ASSOCIATION FOR LEXICOGRAPHY (AFRILEX), AFRICAN LANGUAGES ASSOCIATION OF SOUTH AFRICA (ALASA), BURO VAN DIE WOORDEBOEK VAN DIE AFRIKAANSE TAAL (WAT), DICTIONARY OF SOUTH AFRICAN ENGLISH (DSAE), LINGUISTIC ASSOCIATION OF SOUTHERN AFRICA (LSSA), NASIONALE LEKSIKOGRA-FIESE EENHEDE (NLE's), PAN SUID-AFRIKAANSE TAALRAAD (PanSAT)